Optimasi Komposisi Polietilen Glikol dan Lesitin sebagai Kombinasi Surfaktan pada Sediaan Nanoemulsi Kafein (Optimization of Polyethylene Glycol and Lecithin Composition as Surfactant Combination in the Caffeine Nanoemulsion) - Dessy Dwi Risky Ayuningtias; Dwi Nurahmanto; Viddy Agustian Rosyidi (Pustaka Kesehatan, 2017)
Caffeine is one of alkaloids that have the potential to skin cancer treatment. Caffeine is hydrophilic with log-P value of 0.07 that makes difficult to penetrate to the stratum corneum. Nanoemulsion is one of system which made to increase drug penetration. Oneof the important component in the nanoemulsion is a surfactant that acts as a unifier between the oil and water phases to form one phase that isotropic and thermodynamically stable. The presence of lipophilic component in the surfactant can affect the skin barrierdisturb, thus increasing penetration. The aims of this study was to find the best composition of the PEG-400 and lecithin as surfactant combination to obtain a nanoemulsion that is safe, stable, and increasing penetration of caffeine. The experiment was conducted using a factorial design method which observed responses of flux value and viscosity deviation. The viscosity deviation and flux were analyzed using Design Expert 10.0 trial to determine the optimal formula of caffeine nanoemulsion. The results obtained optimal formula of nanoemulsion that has composition of PEG-400 as 32% and lecithin as 7% . Prediction of viscosity deviation and flux value of optimal formula was 0,034 cP and 0.514 μg cm-2min-1.Keywords: caffeine, nanoemulsion, PEG-400, lecithin